The Meaning of Islamic Media Reporting on The Death Penalty of Rapists in Indonesia - Yuri Alfrin Aladdin; Radita Gora (Jurnal Indonesia Sosial Teknologi, 2024)
Reports on the discourse on the death penalty for rapists are rife throughout 2022 and appear in various top media in Indonesia. Coverage related to this discourse includes the pros and cons among the public regarding the need for a convicted person in a rape case to receive the death penalty. This then becomes the reason for the researcher to examine the policy of the Indonesian Islamic-oriented media, Republika, about the issue of the death penalty for rapists that appears in 2022 because this media’s reports on this case still appear until 2023. This research used Critical Discourse Analysis (CDA) with Norman Fairclough’s model for primary data analysis aiming to interpret the representation of news from Republika regarding the issue of the death penalty for rapists in Indonesia. The subjects and objects of this research are news texts, namely straight news related to the government's discourse on carrying out the death penalty against rapists during the period January 1-31, 2023, on the Republika.co.id news portal. The conclusion of this study is the meaning of reporting on the discourse on the death penalty against rapists in Republika media shows that as a media with an Islamic ideology, referring to Islamic Sharia law, Republika interprets that the death penalty is indeed possible for severe crimes against humanity or those that have broad implications for society such as rape, referring to Surah Al Maidah verse 33